Manifestation Aspects in the Toponymy of Gampongs in Timang Gajah District, Bener Meriah - Trisfayani, Trisfayani; Ginting, Reza Pahlevi; Mahsa, Masithah (SAINTIS Publishing, 2024)
This study aims to analyze the manifestation of toponymy in the villages of Timang Gajah District, Bener Meriah, reflecting the close relationship between place names and the social, cultural, historical, and natural aspects of the local community. A qualitative approach was employed, utilizing techniques such as in-depth interviews, observation, recording, and note-taking for data collection. Data were gathered through interviews with local figures, such as the village head (keuchik), tuha 4, tuha 8, and petue, who possess extensive knowledge of the origins of the village names. Data analysis involved selection, classification, and narrative description to uncover the symbolic meanings embedded in the toponymy. The results indicate that the village names in Timang Gajah District can be categorized into four main types: vegetation toponymy, historical toponymy, bestowed toponymy, and geographical toponymy. Vegetation toponymy reflects the community's relationship with their surrounding environment, while historical toponymy links village names to significant events in local history. Bestowed toponymy, associated with administrative decisions and influential community figures, represents social change and aspirations for progress, whereas geographical toponymy serves as a geographical and administrative marker. This study contributes to the development of toponymic studies, demonstrating how place names in Timang Gajah District not only reflect geographical conditions but also involve cultural, historical, and social dynamics that shape the local community's identity.